Impaired mesial synchronization in temporal lobe epilepsy - Ortega, Guillermo José (2011)
Objective: Temporal lobe epilepsy is commonly associated with synchronous, hyper-synchronous and des-synchronous activity. The aim of the present work is to explore synchronization activity in both mesial areas in temporal lobe epileptic patients during the interictal state. Methods: Using a cluster technique, we analyzed 17 temporal lobe epilepsy patients’ records of foramen ovale electrodes activity during the inter-ictal state. Results: There exists a clear tendency in the mesial area of the epileptic side to be organized as isolated clusters of electrical activity as compared with the contra-lateral side, which is organized in the form of large clusters of synchronous activity. The number of desynchronized areas is larger in the epileptic side than in the contra-lateral side in 16 out of 17 temporal lobe epileptic patients. Conclusions: The mesial area responsible for the seizures is less synchronous than the contra-lateral; the different kind of synchronous organization accounts for a lower synchronization activity at the epileptic side, suggesting that this lack of synchronous cluster organization would favour the appearance of seizures. Significance: Our results shed new light regarding synchronization issues in temporal lobe epilepsy and also it would help in reducing drastically the time of study.